Effect of the tillage system on the floristic composition and the emergence of weeds in Allium sativum - Longás, María de Las Mercedes (2023)
In fragile environments, no-tillage (0T) instead of conventional tillage (CT) is desirable to prevent agroecosystem degradation, but there is little information on its implementation in horticulture. This study aimed to investigate the effects of replacing CT with 0T on floristic composition and weed emergence dynamics in a garlic crop, under the hypothesis that the implementation of a 0T system alters the weed community during the initial stage of the transition. Two experiments were carried out following a randomized complete block design with two treatments (garlic crop grown under 0T and CT). In two subsampling per plot, biweekly destructive weed surveys were carried out. Although both tillage systems presented a similar diversity between systems, these weed communities varied by 36% in their species identity, and it was recorded a higher total weed density under CT (P>0.05). Under 0T, anemophilous Asteraceae, such as Conyza bonariensis and Sonchus oleraceus, tended to increase their presence. Under CT, there was a greater amount of indehiscent fruiting Brassicaceae such as Raphanus sativus and Rapistrum rugosum. The implementation of Vicia villosa as a predecessor crop led to many births due to its capacity for natural reseeding. It is concluded that there are important changes in the species composition and weed emergence patterns immediately after the implementation of 0T compared to CT, suggesting that the filtering pressures exerted by each tillage system favor certain weed species over others. By understanding weed community shifts and critical stages of weed emergence, farmers can improve herbicide application, thereby reducing the excessive use of chemicals and minimizing environmental impact. In addition, this information can help to schedule labor and machinery more efficiently, saving time and production costs.